The impact of Exergames on emotional experience: a systematic review - Marques, Lucas Murrins; Uchida, Pedro Makoto; Barbosa, Sara Pinto (Frontiers in Public Health, 2023)
Background: Gamification has proven to be a significant tool for health promotion, with a particular focus on physical activities such as Exergames, which improve not only physical, but also cognitive health. However, it is still not clear what effect the practice of Exergames has on changing the emotional experience. Purpose: The objective of this systematic review is to evaluate the impact of exergames training on emotional experience. Methods: A systematic search was conducted in the PUBMED and SCOPUS databases. The relevant articles were screened independently by three researchers. Data concerning emotional measures and Exergame practice were extracted for analysis. Results: The search yielded 38 articles, of which 16 were included. Exergames were found to significantly impact happiness, anxiety, depressive symptoms, mental health-related quality of life, self-worth, self-esteem, self-efficacy, perceived behavioral control, vigor, vitality, intrinsic motivation, perceived energy, and relaxation. Conclusion: Our review supports the evidence that the practice of physical activity through Exergames, on the emotional experience generally generates an increase in positive emotions. In this sense, the results found support both the use of Exergames as a leisure activity that promotes wellbeing and emotional regulation, as well as for health promotion, public health, and clinical practice purposes. Our review strongly supports the notion that engaging in physical activity through Exergames generally leads to an increase in positive emotions. As a result, these findings endorse the utilization of Exergames as a leisure activity to promote well-being and emotional regulation. Moreover, Exergames hold potential for health promotion, public health, and clinical practice purposes.